Antenatal glucocorticosteroids treatment: mechanisms of child healths programming - A. V. Shaitarova; L. A. Suplotova (Медицинский совет, 2022)
Synthetic glucocorticoids are widely used in pregnancies at risk of preterm delivery and in pregnant women at risk of having a child with severe 21-hydroxylase deficiency. The positive effects of reducing mortality in preterm and virilisation in girls with congenital adrenal hyperplasia are now unquestionable. The adrenogenital syndrome responding to 21-hydroxylase deficiency is a common, potential fatal disease. Its incidence calculated on the basis of neonatal screening data makes 1 case for 14000 live newborns among the worldwide population, 1 for 9638 – In Russia. DEX passes through the placenta and decreases fetal ACTH production thereby suppressing the fetal production of androgens. The prenatal treatment does not preclude from a life-long treatment in future and it is not prevention of a salt-losing syndrome at the postnatal period, and dexamethasone safety in relation to cognitive development of children prenatally treated with dexamethasone is still up for debate. Adding to the concern is the fact that the doses of DEX that the fetus is exposed to are estimated to be 60 times the normal fetal cortisol level. The glucocorticoid and the mineralocorticoid receptors are highly expressed in the hippocampus, amygdala, and prefrontal cortex. These areas, important for executive functioning, emotional regulation, and memory, are vulnerable to high doses of GCs. Most experimental data from animal have shown that prenatal exposure to synthetic glucocorticoids programs the foetal HPA and may lead to altered susceptibility to metabolic and cardiovascular disease i.e. metabolic syndrome, high blood pressure. Prenatal glucocorticoid exposure also leads to modification of HPAassociated behaviours and cognition.